The Implementation of Simple Project-Based Learning Syntaxes to Improve Vocabulary Elements in Teaching Speaking - Muhammad Husnu; Ahmad yusri; Jatmika Aripadana; Zahratul Fikni (CV. ULIL ALBAB CORP, 2024)
This research aims to enhance students' speaking skills through project-based learning, increasing their engagement and active participation. Using a qualitative approach, data were collected through in-depth interviews and classroom observations involving ten eleventh-grade students at SMAN 1 Sembalun academic year 2024. Thematic analysis was employed to identify critical patterns and themes within the collected data. The findings indicate that students found the project-based method a more enjoyable and meaningful way to practice speaking. They reported increased confidence and engagement in speaking activities due to the opportunities to work in groups and undertake relevant projects. However, some students also faced challenges like group collaboration and time management. This study provides in-depth insights into how project-based learning methods can impact students' speaking skills and offers recommendations for improving the implementation of this approach in the classroom.